SIMPLIFYING CROSS-PLATFORM ARCHITECTURE FOR LOGISTICS APPLICATIONS: A DEVELOPER’S GUIDE - Naveena Pathuri (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY (IJCET), 2024)
This article presents a comprehensive analysis of cross-platform architecture implementation in logistics applications, focusing on optimizing development efficiency while maintaining high-performance standards across multiple platforms. The article examines the fundamental principles of cross-platform frameworks, particularly React Native and Flutter, and their application in modern logistics solutions. The article identifies critical performance bottlenecks and presents effective solutions for GPS tracking, background notifications, and real-time data synchronization. Results demonstrate significant improvements in application performance, including a 40% reduction in memory usage and a 60% enhancement in battery efficiency, while achieving 75% code sharing across platforms. The article also evaluates the integration of emerging technologies such as AI, IoT, blockchain, and augmented reality, providing a framework for future development efforts in logistics applications. These findings contribute to the field by establishing best practices for cross-platform development in logistics, offering practical solutions for common challenges, and outlining future directions for technology integration in supply chain management applications.